Language Training Program : Findings and recommendations of the lexicon evaluation committee - McLaughlin, Sky; Rogers, Jim (Lexicon Evaluation Committee, 2006)

Social Support Networks in Quebec's English-speaking Communities : Building Community Vitality Through Social Capital Strategies - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
This report arises in response to one of the objectives of the “We Can Act” project sponsored by the Community Health and Social Services Network (CHSSN). The CHSSN is a network of 60 community resources, associations, foundations, public institutions and other stakeholders dedicated to the development of partnerships in health and social services for English‐speaking communities in Quebec. The CHSSN promotes knowledge‐based community development as a means for communities to enhance their vitality and improve the health and well‐being of their members. Consistent with the population health approach, CHSSN sponsors projects and partnerships which address health determinants affecting the health status of communities as well as supportive strategies to attain a sustainable health and social service system.
Keywords: Official Language Minority Community (OLMC)

A Study of Women's Needs on the Lower North Shore - Keats, Shannon A. (Coasters Association, 2006)
The mission of the Coasters Association is to develop knowledge of the needs and expectations of the fourteen (14) communities on the Lower North Shore, and act in partnership with community leaders, organizations and stakeholders to design and deliver community strategies, programs and services which respond to the region’s development challenges. In keeping with their mission and providing an opportunity to better the situation of women on the Lower North Shore, a project entitled “A Study of the Needs of Women on the Lower North Shore”, was initiated. The project began on the September 12th, 2005 and ended on March 31st, 2006 (29 weeks). The key goal of the project was to get women involved and talk about the issues facing them and to identify opportunities and lasting solutions, as well as make women aware of the programs and services that are available on the coast, through partnerships with other organizations and to help these women make use of those programs. The purpose of the project was to research information through means of a questionnaire and by organizing focus groups to develop a needs assessment and to establish a coalition (for Phase 2 of the project) to improve the overall status of women on the Lower North Shore of Quebec.

Rapport de Données de Base 2005-2006 : Accés aux services de santé et aux services sociaux en anglais au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

The Baseline Data Report 2005-2006 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)